Real time PCR quantification of frataxin mRNA in the peripheral blood leucocytes of Friedreich ataxia patients and carriers. Issue 7 (16th June 2004) - Pianese, L; Turano, M; Lo Casale, M S; De Biase, I; Giacchetti, M; Monticelli, A; Criscuolo, C; Filla, A; Cocozza, S
Abstract : The most common causative mutation of Friedreich ataxia (FRDA) is the unstable hyperexpansion of an intronic GAA triplet repeat that impairs frataxin transcription. Using real time quantitative PCR, we showed that FRDA patients had residual levels of frataxin mRNA ranging between 13% and 30% and that FRDA carriers had about 40% of that of controls. Asymptomatic carriers also showed reduced frataxin mRNA levels. We found an inverse correlation between the number of GAA repeats and frataxin mRNA levels. Real-time quantitative PCR may represent an alternative assay for FRDA molecular diagnosis.